Links between TAFE and Industry A TAFE Perspective. A Discussion Paper - Hall, William C.; TAFE National Centre for Research and Development, Ltd., Leabrook (Australia). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This paper considers links between the Technical and Further Education (TAFE) system in Australia and industry and raises issues for discussion. The first section describes TAFE and its background, followed by descriptions of the links between TAFE and industry at the national, system, college, and individual levels. According to the research, national links have been developed directly through structural changes and less directly through political pressure. System links have developed through structural changes also. Common features of these links are the separation of policy formulation from delivery, integration of some Commonwealth activity within the state/territory structure, a reduction in the number of advisory bodies, an emphasis on cost recovery--especially when providing training to industry, and attempts to break the on-the-job/off-the-job dichotomy. A major curriculum push in all systems and across industry is for the widespread introduction of competency-based training. Colleges are linked to industry in many ways, especially through shared equipment, facilities, and staff, and development of courses for industries. In addition, individual lecturers have made links with particular businesses through consultancies. Issues to be explored in the future include the definition of TAFE and the use of its acronym, planning, changes needed, college-based and industry-based programs, controls, student needs, and social justice. (KC)
Availability: TAFE National Centre for Research and Development, Attn: Sales, 252 Kensington Road, Leabrook, South Australia 5068, Australia.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competency Based Education; Continuing Education; Developed Nations; Education Work Relationship; Educational Needs; Educational Philosophy; Educational Policy; Educational Practices; Foreign Countries; Industry; Policy Formation; Postsecondary Education; School Business Relationship; Technical Education; Vocational Education; TAFE (Australia); Opinion Papers